A Case Study on Colombian Mitigation Actions - Delgado, Ricardo; Cadena, Angela Inés; Espinosa, Mónica; Peña, Catalina; Salazar, Mateo (Taylor & Francis, 2014)
This paper introduces the Colombian case study developed under the Mitigation Actions Plans and Scenarios Initiative and the Endesa Colombia Electric Vehicles Initiative. It is aimed to consider the use of electricity in the transportation sector, particularly in the city of Bogotá, Colombia. A model for assessing the economic and environmental impacts of the introduction of electric vehicules for private, utility and public services is proposed. Diversification of the energy basket by introducing electricity in the transportation sector is a plausible development strategy for the country. Colombian electricity is relatively clean because of the high hydro component in the generation basket; therefore the substitution of fossil fuels for electricity represents net savings in emissions of greenhouse gases as well as a reduction of particulate matter. The increase in electricity demand as a result of this new use is not high enough to stress installed generation capacity or supply security.